The Role of Productive Zakat in the Development of MSMEs in Ngronggot District, Nganjuk Regency (Study on LAZISNU MWCNU Ngronggot) - Badrus Sholeh; A'Rasy Fahrullah (GERASI INSAN NUSANTARA, 2026)
Indonesia, as a developing country, still faces the problems of poverty and income inequality. Zakat, as an Islamic economic instrument, plays a strategic role in addressing these issues, particularly through a productive zakat approach. This study aims to analyze the role of productive zakat in the development of MSMEs in Ngronggot District, Nganjuk Regency through LAZISNU MWCNU Ngronggot. The research method used is a qualitative case study approach. Data collection techniques were carried out through observation, interviews, and documentation. The results show that productive zakat plays a positive role in increasing business turnover, assets, and the welfare of mustahik. However, there are still obstacles such as limited mentoring and managerial capabilities of beneficiaries. This study confirms that productive zakat can be an effective instrument of economic empowerment if managed optimally and sustainably